Pengaruh Inovasi Digital dan Transparansi Terhadap Kepatuhan Akad Murabahah pada Bank Syariah Iidonesia Di KC Simprung: The Influence of Work-Life Balance, Work Stress and Work Discipline on Employee Performance in FnB Companies - Nuraliza, Della; Riska, Ai Alpha Nurul; Alimnaesti, Eka (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The development of digital technology and transparency in Islamic banking has generated important implications for compliance in the implementation of murabahah contracts. This study aims to examine the impact of digital innovation and transparency on murabahah contract compliance at Bank Syariah Indonesia (BSI), Simprug Branch Office. A quantitative research approach was employed, with data collected through questionnaires distributed to 30 murabahah financing customers who utilize BSI’s digital services. The data were analyzed using multiple linear regression techniques with the assistance of statistical software. The findings indicate that digital innovation has a positive and significant effect on murabahah contract compliance. Transparency also demonstrates a positive and significant impact on murabahah contract compliance. Furthermore, digital innovation and transparency simultaneously show a significant influence on murabahah contract compliance. These results suggest that the implementation of digital technology accompanied by transparent information disclosure can enhance the conformity of contract execution with Sharia principles. Therefore, strengthening transparent and integrated digital aspects is a strategic element in maintaining Sharia compliance and increasing customer trust in Islamic banking.